PENGARUH LKS BERORIENTASI PEMBELAJARAN DOUBLE LOOP PROBLEM SOLVING (DLPS) TERHADAP KOMPETENSI FISIKA SISWA KELAS XI SMAN 13 PADANG - Mailen Sasri; Syakbaniah Syakbaniah; Ermaniati Ramli (PILLAR OF PHYSICS EDUCATION, 2015)
Low competence due to the physics student learning in school is not associated with the problems everyday life. This is because the problem solving ability of students are still low. The way to mitigate this problem is to use a problem-based learning worksheets. LKS designed double-loop learning-oriented problem solving (DLPs). This study aims to determine the effect of the application of learning-oriented LKS (DLPs) the competence of physics. Samples were taken using cluster random sampling technique and obtained XI MIA 1 as an experimental class and class XI MIA 2 as the control class.The results showed that the average value of student competencies in the realm of knowledge, attitudes and skills for the experimental class is 76.6; 80.5; and 82.21 and for the control class is 70.37; 75.18; and 76.28. Test for equality of two average in all three domains, using a statistical t-test at the 0.05 significance level, shows that there is a significant difference, this difference is believed to be due to the influence of learning-oriented LKS (DLPs) the competence of physics class XI SMAN 13 Padang